Conceptional and Theoretical Fundamentals of Regulation of the Labour Market in the Border Region (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The essence of the concept of the regional labor market is opened in the article. The labor market regulation is known as one of the main problem of socio-economic development of the region and the author prompted his own vision of this category and developed strategic directions and tasks of the labor market regulation in the border region.Features of state regulation of the labor market in the developed world are described here also. It is revealedthe role of institutional provision of labor market regulation and the effectiveness of self-regulation mechanisms.In this research it is defined the necessity of transformation of the system, which provides labor market regulations to guide the formation of the regulated labor market.
Keywords: labor market, the regional labor market, the border region, labor market regulation, the economically active population